All you need to know about the music business. - Passman, Donald S., 1945- (New York : The Free Press, 2009)
Since the advent of file-sharing technology in the late 1990s, the music industry has been challenged to reinvent itself. What has it done? How have the record labels repositioned themselves to cope with these massive changes? How does all this affect creative artists? No one understands the music industry -- from the technology, to the legalities, to the new industry practices -- better than veteran music lawyer Donald Passman. In this completely revised and updated seventh edition of All You Need to Know About the Music Business, which the Los Angeles Times called the industry bible and which has sold hundreds of thousands of copies over the last eighteen years, Passman offers executives and artists, experts and novices alike the essential information they need not only to survive in these volatile and exciting times, but also to thrive. Drawing on his unique, up-to-the-minute experience as one of the most trusted advisors in the industry, Passman offers new information on: - The new
360 model of record deals, wherein record companies share in nonrecord revenue - The Copyright Royalty Board's latest decisions regarding online transmissions - The developing customs on new technologies such as streaming on demand, ringtones, and digital downloads - Updates on recording and publishing deals, as well as film music He also gives guidance on fundamental issues, such as how to: - Select and hire a winning team of advisors -- personal and business managers, agents, and attorneys -- and structure their commissions, percentages, and fees in a way that will protect you and maximize these relationships - Master the big picture and the finer points of record deals - Navigate the ins and outs of songwriting, music publishing, and copyrights - Maximize concert, touring, and merchandising deals Everyone in the business -- musicians, songwriters, entertainment lawyers, agents, promoters, publishers, managers, record company executives -- is scrambling to figure out what's going to happen
In the future, and Passman is in the thick of these changes. Anyone interested in a music career will need this comprehensive and crucial guide to making it in one of the world's most dynamic industries.
Keywords: Muziekindustrie